Planejamento estratégico de relações públicas para o setor de marketing da FAMETRO - Gouvea, Ana Milena de Oliveira (Brasil, 2022)
Understanding the universe of organizations and how they dialogue with their targeted audiences is one of the tasks performed by the Public Relations professional. With the advance of globalization, the need for strategic communication in organizations is increasingly evident, and this communication seeks to exercise exchange and build relationships with their audiences of interest. For that to happen, developing strategic planning performed by a Public Relations professional becomes the first step because it allows tracing objectives and strategies focused on communication and applying medium and long-term actions to achieve these objectives. Therefore, the main goal of this paper is to develop a strategic public relations plan for the marketing sector of FAMETRO. This paper is an applied research of exploratory nature, with a qualitative approach, conducting theoretical and bibliographic surveys and semi-structured interviews to develop a diagnosis for planning. The planning presented in this work made it possible to identify the scenario of internal communication in the marketing sector. The interviews and the diagnosis elucidated the communication flows that needed to be improved while the results clarified the main communication challenges faced by the sector.